Conspiracy Theories. Some philosophical points made starting from the semiotic texture (but not only) in which we move - Silvestri, Filippo (Rivista Italiana di Filosofia del Linguaggio, 2022)
Several philosophical studies of conspiracy theories refer to some observations made by Karl Popper in 1948. To this day, Popper’s argument remains a cornerstone for anybody approaching for the first time a philosophical context of analysis, where the philosopher’s study occupies a middle position between the philosophy of history and other epistemological arguments. Today, the investigation includes many other philosophical scenarios and the growing interest for this topic does not stem exclusively from the recent pandemic and its political and health management. The suspicion that events are orchestrated by dark forces weighs on a vast political spectrum spanning the management of immigration and the wars breaking out across the planet. Several conspiracy theories have emerged across history with some turning into actual State policies. This is the case of the persecution of Jews by the Nazi regime, that of political opponents in Stalin’s USSR, and the theories about the death of JFK and the Moon landing. This study maps some philosophical analyses and their semiotic aspects. After unpacking Popper’s argument, it moves to more recent Italian researches. The goal of the paper is to outline at least some analytical trends to try to capture the general, post-truth climate that is a breeding ground of countless conspiracy theories, showing its limitations and attempting to understand that nobody can claim to be immune to such theoretical temptations.